2015
DOI: 10.1021/acs.chemrestox.5b00338
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl Saligenin Phosphate Induced Caspase-3 and c-Jun N-Terminal Kinase Activation in Cardiomyocyte-Like Cells

Abstract: At present, little is known about the effect(s) of organophosphorous compounds (OPs) on cardiomyocytes. In this study we have investigated the effects of phenyl saligenin phosphate (PSP), two organophosphorothioate insecticides (diazinon and chlorpyrifos) and their acutely toxic metabolites (diazoxon and chlorpyrifos oxon) on mitotic and differentiated H9c2 cardiomyoblasts. OP-induced cytotoxicity was assessed by monitoring MTT reduction, LDH release and caspase-3 activity. Cytotoxicity was not observed with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…All activity was blocked by co-treatment with 100 μM ZDON. To determine whether this reflected covalent adduct formation between TG2 and PSP, recombinant TG2 was incubated with a dansylamine-labelled analogue of PSP, which had previously been used to identify PSP adducts in cardiomyocyte-like cells (Felamban et al 2015 ). The gel images in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All activity was blocked by co-treatment with 100 μM ZDON. To determine whether this reflected covalent adduct formation between TG2 and PSP, recombinant TG2 was incubated with a dansylamine-labelled analogue of PSP, which had previously been used to identify PSP adducts in cardiomyocyte-like cells (Felamban et al 2015 ). The gel images in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…( 51 , 52 ) Heat shock protein β-1 (also known as HSP-27) is a member of a small heat shock protein family and is involved in the regulation of apoptosis, protection of cells against oxidative stress. ( 53 ) Interestingly, it is reported that heat shock protein β-1 is able to prevent α-synuclein aggregation in the culture of neurons overexpressing α-synuclein and thus increases neuron survival. ( 54 ) Thus, the increase in expression levels of inorganic pyrophosphatase and heat shock protein β-1 may play a neuroprotective role in the DG after ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cardiomyocyte survival and death are regulated by extracellular ligands, cytokines, and growth factors that bind to cell surface receptors and induce intracellular specific signal transduction pathways [51]. Cardiac dysfunction usually occurs as a consequence of inflammatory, oxidative stress, and apoptosis mechanisms mediated by MAPK signaling pathways, and ERK, JNK, and p38-MAPK activation has been demonstrated in heart failure models [51]. Furthermore, the effects of DZN, phenyl-saligenin-phosphate (PSP), and CPF and their toxic metabolites (diazoxone and CPF-oxone) on H9c2 cardiomyoblasts were investigated.…”
Section: Organophosphorus Compound-induced Cardiovascular Diseases Armentioning
confidence: 99%
“…Furthermore, the effects of DZN, phenyl-saligenin-phosphate (PSP), and CPF and their toxic metabolites (diazoxone and CPF-oxone) on H9c2 cardiomyoblasts were investigated. Forty-eight h after exposure to DZN, diazoxone, or CPF-oxone (200 μM), no cytotoxicity was found in H9c2 cells [ 51 ]. However, CPF induced cardiotoxicity in H9c2 at a dose of over 100 μM.…”
Section: Organophosphorus Compound-induced Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation